Partial Predictability in Avoidance Acquisition and Expression of Wistar-Kyoto and Sprague-Dawley Rats: Implications for Anxiety Vulnerability in Uncertain Situations - Miller, Daniel Paul; Allen, Michael Todd; Servatius, Richard J. (Frontiers in Psychiatry, 2020)
Individual differences or vulnerabilities must exist which bias some individuals towards psychopathology while others remain resilient in the face of trauma. Recent work has studied the effects of uncertainty on individuals expressing behavioral inhibition (BI). The current study extended this work with uncertainty to Wistar Kyoto (WKY) rats which are a behaviorally inhibited inbred strain that models learning vulnerabilities for anxiety disorders and posttraumatic stress disorder (PTSD). WKY rats exhibit superior avoidance performance in a signaled bar press avoidance task in which a tone conditioned stimulus (CS) signals a foot shock unconditioned stimulus (US) when compared with non-inhibited Sprague Dawley (SD) rats. In addition, WKY rats express enhanced eyeblink conditioning. Recent work with behaviorally inhibited humans has indicated that this enhanced eyeblink conditioning is more evident in conditions that insert CS or US alone trials into CS-US paired training, resulting in uncertain and suboptimal learning conditions. The current study examined the effects of partial predictability training, in which the CS signaled the US only one-half of the time, on the acquisition and expression of avoidance. Standard training with a fixed 60 s CS which predicted shock on 100% of trials was compared with training in which the CS predicted shock on 50% of trials (partial predictability) using a pseudorandom schedule. As expected, WKY rats acquired avoidance responses faster and to a greater degree than SD rats. Partial predictability of the US essentially reduced SD rats to escape responding. Partial predictability also reduced avoidance in WKY rats; however, adjusting avoidance rates for the number of potential pairings of the CS and US early in training suggested a similar degree of avoidance expression late in the last session of training. Enhanced active avoidance expression, even in uncertain learning conditions, can be interpreted as behaviorally inhibited WKY rats responding to the expectancy of the shock by avoiding, whereas non-inhibited SD rats were responding to the presence of the shock by escaping. Future work should explore how WKY and SD rats as well as behaviorally inhibited humans acquire and extinguish avoidance responses in uncertain learning situations.